2015
DOI: 10.1007/s00405-014-3474-8
|View full text |Cite
|
Sign up to set email alerts
|

How uncomplicated total thyroidectomy could aggravate the laryngopharyngeal reflux disease?

Abstract: Swallowing, voice disorders, throat discomfort and subjective neck discomfort are usually reported by patients with a known thyroid nodule and are correlated to nodular thyroid disease itself. Moreover, in endemic goitrous areas, total thyroidectomy (TT) is the most frequently performed surgical procedure. We are used to relate swallowing, voice and throat discomfort to the mechanical effects of nodular goiter or to thyroidectomy itself, but in both these cases the relationship between symptoms and the thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…It has been suggested that laryngopharyngeal reflux (LPR) also plays a role in patients with post-thyroidectomy syndrome [7,8]. LPR is a retrograde flow of gastric and duodenal contents into the pharynx or larynx above the upper esophageal sphincter (UES).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that laryngopharyngeal reflux (LPR) also plays a role in patients with post-thyroidectomy syndrome [7,8]. LPR is a retrograde flow of gastric and duodenal contents into the pharynx or larynx above the upper esophageal sphincter (UES).…”
Section: Introductionmentioning
confidence: 99%
“…Authors who have compared conventional open thyroidectomy to robotic techniques, minimally invasive thyroid surgery, and subfascial approach to the thyroid reported a statistically significant increase of swallowing impairments in the conventional group ( 10 , 11 , 16 , 33 , 37 , 38 , 52 , 53 ). Additionally, laryngopharyngeal reflux (LPR) could influence postsurgical swallowing complaints ( 6 , 13 , 25 , 54 , 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly results were observed for dysphagia except for patients who underwent videoassisted TT (symptoms ameliorated already 1 month after TT). Cusimano et al [26] studied patients Fig. 3 The late postoperative mean scores stratified by groups of thyroid weight.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly results were observed for dysphagia except for patients who underwent videoassisted TT (symptoms ameliorated already 1 month after TT). Cusimano et al [ 26 ] studied patients affected by reflux to explain the role of thyroidectomy in persistent neck symptoms. The authors speculated that surgery may worsen the reflux disease by reducing antireflux systems and suggests including reflux disease as cause for neck postoperative discomforts.…”
Section: Discussionmentioning
confidence: 99%